A Direct Methane Fuel Cell with Double-Layered Electrolyte Using Proton Conducting Oxide. (30th May 2017) - Okuyama, Yuji; Kawano, Shigemichi; Sakai, Go; Matsunaga, Naoki; Mizutani, Yasunobu
Abstract : BaCe0.8 Y0.2 O3-δ (BCY) has a high proton conductivity, but less stable against carbon dioxide. La0.9 Sr0.1 Yb0.8 In0.2 O3-δ (LSYbIn) is chemically stable, but not as conductive as BCY. In this study, the performance of a methane fuel cell using BCY and LSYbIn as the electrolyte was evaluated. The fuel cell using BCY showed a short-term degradation. On the other hand, the fuel cell using LSYbIn showed a high capability using methane. The protonic ceramic fuel cell with a double-layered electrolyte was developed to improve of the chemical stability toward methane and the fuel cell performance. LSYbIn was used as the fuel side intermediate layer of the fuel cell using BCY for protection from methane. The fuel cell with a double-layered electrolyte suppressed the degradation by methane.